Highlights on Several Underestimated Topics in Palliative Care 2017
DOI: 10.5772/intechopen.69663
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis Prediction Models and their Clinical Utility in Palliative Care

Abstract: Prognosis prediction is a clinically relevant issue to facilitate optimal decision-making for both physicians and patients with cancer. Many previous studies revealed that prognosis prediction based on the physician's intuition and/or clinical experience is inaccurate and often optimistic, which means that there is a tendency to overestimate patient survival in daily clinical practice. In recent decades, many eforts have been made to develop prognosis prediction models which aid physicians to make more accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Hence predicting the prognosis is vital for improved end of life care. Clinical Prediction of survival is based on the specific clinician and is a subjective opinion and hence it is important to develop objective prognosis prediction models using prognostic factors which include symptom and laboratory data [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence predicting the prognosis is vital for improved end of life care. Clinical Prediction of survival is based on the specific clinician and is a subjective opinion and hence it is important to develop objective prognosis prediction models using prognostic factors which include symptom and laboratory data [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Healthcare data that is routinely collected provides increasing opportunities for valuable insights to be obtained using Artificial Intelligence techniques and data driven methods [74]. Research studies have shown that incorporating AI into health care has helped provide for less aggressive care in ICU admissions, administering a ventilator or resuscitation procedure at end of life [11][75] [76] [77]. Applications of Machine Learning in pain care research are limited due to the availability of data.…”
Section: Recent Related Studies and Enhancements Possiblementioning
confidence: 99%
“…Several userfriendly clinical tools have been developed in previous studies, such as the palliative prognostic score, the palliative prognostic index, and prognostic in palliative care study predictor models [49][50][51]. Detailed discussion regarding this topic is described elsewhere [52].…”
Section: Prognosis Predictionmentioning
confidence: 99%